PENGGUNAAN MODEL PEMBELAJARAN TIME TOKEN TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP - Beni Junedi; Novita Anggiani (Universitas Islam Sumatera Utara, 2018)
Abstract. This research was motivated by the understanding of mathematical concepts class VIII SMPN 3 Pasir Penyu still low. This study aims to determine student’s understanding of mathematical concepts using time token learning model is better than the students understanding of mathematical concepts using convensional learning in class VIII SMPN 3 Pasir Penyu. This study design was randomized control group only design. This study population was students all class VIII, the sample is class VIII3 and VIII4. Data were analyzed using test-t, analysis result obtained tcount ttable is 2.995 2.002, it can be concluded that the understanding of the mathematical concepts of student with the use of time token learning model better than an understanding of the mathematical concepts of students with the use of convensional learning in class SMPN 3 Pasir Penyu.Keywords: Time token, understanding of mathematical concepts.